Effect of flow regime on the architecture of a pseudomonas fluorescens biofilm - Pereira, Maria Olívia (2002)
A comparison of the effects of laminar versus turbulent flow regime on the characteristics of a single-species biofilm is presented. The study was carried out by growing Pseudomonas fluorescens biofilms in a flow cell and studying the different layers of the biological matrix with a confocal laser-scanning microscope. The following conclusions were obtained: i) a higher concentration of cells was found in the upper layers of the microbial films than in their inner layers, regardless of the flow regime; ii) the fraction of cells in the overall biofilm mass decreased with time as the film grew; and iii) under laminar flow the total number of cells was higher than in biofilms formed under turbulent flow, but the latter had a higher number of cells per unit volume. Such conclusions, together with the fact that the biofilms were more dense and stable when formed in contact with turbulent flows, favor the design of more compact and efficient biofilm reactors operating in turbulent conditions.